2018
DOI: 10.1057/s41284-018-0142-5
|View full text |Cite
|
Sign up to set email alerts
|

Do sports stadiums generate crime on days without matches? A natural experiment on the delayed exploitation of criminal opportunities

Abstract: Crime pattern theory claims that busy places generate crime through immediate and delayed exploitation. In delayed exploitation, offenders notice criminal opportunities during opening hours but return to exploit them later. This study investigates delayed exploitation by testing whether soccer stadiums locally increase police recorded property crime on non-game days. A soccer stadium closure created a natural experiment. We estimate linear regression differencein-difference models to compare crime rates on non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Second, this paper advances the emerging literature on negative externalities of professional sport facilities, and games played in them. Examples include studies found that the presence of sport franchises and the hosting of games is associated with increases in crime (Mares & Blackburn, 2019; Montolio & Planells-Struse, 2018; Pyun, 2019; Pyun & Hall, 2019; Vandeviver et al, 2019), congestion (Humphreys & Pyun, 2018; Propheter, 2020), and air pollution (Locke, 2018). Humphreys and Ruseski (2019) found that sports facility construction has adverse impacts on newborns through environmental damage.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Second, this paper advances the emerging literature on negative externalities of professional sport facilities, and games played in them. Examples include studies found that the presence of sport franchises and the hosting of games is associated with increases in crime (Mares & Blackburn, 2019; Montolio & Planells-Struse, 2018; Pyun, 2019; Pyun & Hall, 2019; Vandeviver et al, 2019), congestion (Humphreys & Pyun, 2018; Propheter, 2020), and air pollution (Locke, 2018). Humphreys and Ruseski (2019) found that sports facility construction has adverse impacts on newborns through environmental damage.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This intersection of the routine activities of potential offenders and victims results in elevated levels of crime risk, and these tend to cluster in space and time (Brantingham and Brantingham, 1995;Felson, 2006;van Sleeuwen et al, 2021a). While a considerable body of research has already examined these spatiotemporal clusters of crime (Andresen et al, 2017;Ariel et al, 2019;Braga et al, 2019;Vandeviver et al, 2019;Weisburd et al, 2017), only a few studies have examined temporal aspects of crime and police (e.g., Ratcliffe, 2002).…”
Section: Temporal Aspects Of Police Presence and Simple Indicators Of...mentioning
confidence: 99%
“…Billings and Depken (2012) conducted a similar study in which they also controlled for distance to a stadium in Charlotte, North Carolina, and found an increase in property crimes up to a mile away and a multipurpose arena that experienced a significant increase in violent crimes up to two miles away when compared to days when the facilities were not used. Other, similar nonparametric, econometric, and Bayesian approaches to the study of mass gatherings and crime have been conducted at this more granular level at stadia across the UK (see Kurland, Johnson, & Tilley, 2014; Kurland et al, 2014, 2018; Marie, 2016; Ristea, Kurland, et al, 2018), the United States (see Klick & MacDonald, 2020; Kurland & Piza, 2018; Menaker et al, 2019; Ristea et al, 2020), Canada (see Ristea et al, 2018), Belgium (Vandeviver et al, 2019), and Spain (Montolio & Planells-Struse, 2015, 2019) with similar findings.…”
Section: Sports Violence and Crimementioning
confidence: 99%